2020
DOI: 10.3390/ijms21218300
|View full text |Cite
|
Sign up to set email alerts
|

Priming with HDAC Inhibitors Sensitizes Ovarian Cancer Cells to Treatment with Cisplatin and HSP90 Inhibitors

Abstract: Ovarian cancer is the fifth leading cause of cancer deaths. Chemoresistance, particularly against platinum compounds, contributes to a poor prognosis. Histone deacetylase inhibitors (HDACi) and heat shock protein 90 inhibitors (HSP90i) are known to modulate pathways involved in chemoresistance. This study investigated the effects of HDACi (panobinostat, LMK235) and HSP90i (luminespib, HSP990) on the potency of cisplatin in ovarian cancer cell lines (A2780, CaOV3, OVCAR3 and cisplatin-resistant sub-clones). Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Considering the importance of biological changes during head and neck cancer treatment, we demonstrated the mecha- and induces apoptosis in cells with the combination of cisplatin (Yousafzai et al, 2019). Although few studies describe the deregulation of HDACs associated with chemoresistance, several works explore the administration of HDAC inhibitors to overcome cisplatin chemoresistance in ovarian cancer, HNSCC, adenoid cystic carcinoma, and lung cancer (Almeida et al, 2017;Iannelli et al, 2020;Rodrigues Moita et al, 2020;Sun et al, 2019). Consequently, targeting HDACs and SIRT1 might be a promising strategy to manage the chemoresistance of HNSCC and perhaps other cancer types.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering the importance of biological changes during head and neck cancer treatment, we demonstrated the mecha- and induces apoptosis in cells with the combination of cisplatin (Yousafzai et al, 2019). Although few studies describe the deregulation of HDACs associated with chemoresistance, several works explore the administration of HDAC inhibitors to overcome cisplatin chemoresistance in ovarian cancer, HNSCC, adenoid cystic carcinoma, and lung cancer (Almeida et al, 2017;Iannelli et al, 2020;Rodrigues Moita et al, 2020;Sun et al, 2019). Consequently, targeting HDACs and SIRT1 might be a promising strategy to manage the chemoresistance of HNSCC and perhaps other cancer types.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with our findings, it has been demonstrated that increased HDAC1 expression occurs in laryngeal squamous cell carcinoma (LSCC) after treatment with 5‐fluorouracil and cisplatin, and the HDAC1 knockdown significantly restores the sensitivity of LSCC cells (Ding et al, 2021), as well as SIRT1 knockdown in chemoresistant lung cancer cells, substantially reduces cell viability, increases sensitivity, and induces apoptosis in cells with the combination of cisplatin (Yousafzai et al, 2019). Although few studies describe the deregulation of HDACs associated with chemoresistance, several works explore the administration of HDAC inhibitors to overcome cisplatin chemoresistance in ovarian cancer, HNSCC, adenoid cystic carcinoma, and lung cancer (Almeida et al, 2017; Iannelli et al, 2020; Rodrigues Moita et al, 2020; Sun et al, 2019). Consequently, targeting HDACs and SIRT1 might be a promising strategy to manage the chemoresistance of HNSCC and perhaps other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Luminespib is a novel heat shock protein (Hsp90) inhibitor that inhibits the proliferation of various human tumour cell lines and induces Luminespib is a novel Hsp90 inhibitor that inhibits the proliferation of various human tumour cell lines, induces cell cycle arrest and apoptosis, and depletes client proteins in human cancer cells [19] . It is currently commonly used in the treatment of pancreatic cancer and non-small-cell lung cancer [20] .One study experimentally explored the nding that pre-incubation with Panobinostat and Luminespib 48 hours before cisplatin enhanced the potency of cisplatin in all cell lines by inducing apoptosis and affecting the expression of apoptosis-related genes and proteins, sensitising OC cells to Luminespib or cisplatin treatment and affecting the development of cisplatin resistance, or even completely reversing Cisplatin resistance, which may help to improve OC treatment [21] .Combination with our studies, Luminespib may play an important role in the treatment of drug-resistant OC.…”
Section: Discussionmentioning
confidence: 99%
“…This potential synergistic effect of HDACis warrants further investigation to determine if HR proficient tumours can be sensitised to PARP inhibition. Interestingly, Panobinostat may also be able to impart re-sensitisation of platinum-based compounds as demonstrated in cisplatin resistant ovarian cancer cell lines [ 113 ], possibly by rewiring these cells to a BRCA-deficiency like phenotype.…”
Section: Epigenetic Treatments In Gynaecological Cancersmentioning
confidence: 99%